2015
DOI: 10.1007/s11325-015-1161-7
|View full text |Cite
|
Sign up to set email alerts
|

Home-use servo-ventilation therapy in chronic pain patients with central sleep apnea: initial and 3-month follow-up

Abstract: PurposeOpioid treatment of non-malignant chronic pain can result in hypoxemia, hypercarbia, and central sleep apnea. The aim of this study was to determine the initial efficacy of auto servo-ventilation (ASV) and after 3 months of home use.MethodsThis prospective multicenter interventional study recruited chronic pain patients prescribed ≥100 morphine equivalents for at least 4 months.ParticipantsFollowing full-night polysomnography (PSG) to confirm the presence of sleep-disordered breathing, patients were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…If SDB is suspected or confirmed and the patient is being prescribed COT, one should consider a number of risk mitigation interventions including: Opioid dose reduction Trial of nonopioid therapies (NSAIDs, antiepileptic drugs, physical therapy, antidepressants, etc.) in lieu of opioids Avoiding use of benzodiazepines, sedatives, and hypnotics Caution against alcohol use Sleep medicine consultation and treatment of SDB (for example there is evidence of the efficacy of adaptive cervo‐ventilation and bilevel positive airway pressure ventilation for CSA in patients on COT ) …”
Section: Risk Assessment and Mitigation Strategiesmentioning
confidence: 99%
“…If SDB is suspected or confirmed and the patient is being prescribed COT, one should consider a number of risk mitigation interventions including: Opioid dose reduction Trial of nonopioid therapies (NSAIDs, antiepileptic drugs, physical therapy, antidepressants, etc.) in lieu of opioids Avoiding use of benzodiazepines, sedatives, and hypnotics Caution against alcohol use Sleep medicine consultation and treatment of SDB (for example there is evidence of the efficacy of adaptive cervo‐ventilation and bilevel positive airway pressure ventilation for CSA in patients on COT ) …”
Section: Risk Assessment and Mitigation Strategiesmentioning
confidence: 99%
“…Prevalence of SDB is known to be high in these patients and is often symptomatic (40,41). Although a few clinical studies have shown that ASV could control SDB (CSA) in patients under chronic high dose opioid treatment (18,19,42), there are no randomized trials showing a long term improvement in either symptom scales, HRQL or survival. Many questions therefore remain, such as: should we screen patients under opioids for SDB?…”
Section: Discussionmentioning
confidence: 99%
“…The recent SERVE-HF study questioned the use of ASV in cardiac failure: in patients with chronic heart failure (CHF) and a left ventricular ejection fraction (LVEF) ≤45%, ASV was associated with an increase in mortality (9). Although designed for CSB, use of ASV has drifted in clinical practice to other indications such as emerging sleep apnea (10)(11)(12)(13)(14)(15)(16), central or mixed apnea syndromes (17), either idiopathic, drug-induced (18)(19)(20)(21)(22)(23), or associated with neurologic disorders (10)(11)(12)24). Use of ASV in these indications does not rely on a high level of evidence of efficacy or benefit on outcomes such as survival or health-related quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, most studies have shown that ASV is more effective than other therapies, including CPAP and BPAP, in reducing central events, although this finding is not universal . Long‐term use of ASV has been reported in two studies, confirming sustained control of SDB and good adherence to therapy . However, there is a lack of data concerning the impact of PAP including ASV on clinical outcomes such as quality of life or mortality.…”
Section: Adaptive Servoventilationmentioning
confidence: 98%
“…23,26 Long-term use of ASV has been reported in two studies, confirming sustained control of SDB and good adherence to therapy. 24,27 However, there is a lack of data concerning the impact of PAP including ASV on clinical outcomes such as quality of life or mortality.…”
Section: Opioid-induced Central Apnoeamentioning
confidence: 99%